East Asian and US educators' reflections on how stigmatization affects their relationships with parents whose children have disabilities: Challenges and solutions. (February 2017) - Kayama, Misa; Haight, Wendy; Ku, May Lee Mary; Cho, Minhae; Lee, Hee Yun
Abstract: Stigmatization is a culturally widespread social justice challenge with broad implications for the development of children. This study examines the reflections of elementary school educators in Japan, South Korea, Taiwan and the US on how stigma affects their relationships with parents whose children have disabilities and how they respond to these challenges. We conducted cross-cultural analyses of individual, audio recorded interviews with 26 Japanese, 43 Korean, 16 Taiwanese and 18 US educators, including school social workers. Educators from all four cultural groups characterized the development of collaborative relationships with parents as critical to supporting the school success of children with disabilities. They also described challenges posed by stigmatization to those relationships, and solutions to those challenges. Japanese educators watched over, carefully guided, and expressed empathy to parents responding to stigmatization. South Korean educators avoided openly indicating children's struggles to parents, but provided them with education about disabilities to counter misperceptions. Taiwanese educators exercised patience with parents who expressed distress due to stigmatization, and concealed their own negative emotional responses to such displays. US educators engaged parents through fact-oriented, solution-focused responses to children's struggles. The perspectives of educators from diverse contexts can be used to identify cultural blind spots, and develop effective culture- and stigma-sensitive strategies to build relationships with parents to better support children with disabilities. Highlights: Educators discussed their relationships with parents of children with disabilities. Japanese educators watched over, carefully guided, and showed empathy to parents. South Korean educators provided formal education to parents about disabilities. Taiwanese educators exercised patience with parents who expressed distress. US educators engaged parents through fact-oriented, solution-focused responses.